Infernal devices. [Vol.] 1, Clockwork angel - Clare, Cassandra (Clare, Cassandra. Infernal devices (Graphic novel), 2012)
When sixteen-year-old orphan Tessa Fell's older brother suddenly vanishes, her search for him leads her into Victorian-era London's dangerous supernatural underworld, and when she discovers that she herself is a Downworlder, she must learn to trust the demon-killing Shadowhunters if she ever wants to learn to control her powers and find her brother.